Giftedness and gifted education: A systematic literature review - Francesca Baccassino; Stefania Pinnelli (Frontiers in Education, 2023)
The present study aims to discuss the state of the art inherent in pedagogical-didactic research on the education of gifted students. To this end, a systematic review of scientific texts published between 2011 and 2021 was carried out. The present article is organized as follows: introduction to the topic; definition of the objectives, research questions, and methodological protocol; selection, evaluation, and synthesis of the abstract studies; discussion and evaluation of the results; and conclusions. Multiple tools for identifying the gifted students (for use by psychologists, pedagogists, educators, and teachers) emerge from the findings of the present study. The texts highlight numerous instructional and educational programming models for gifted students in all school grades. The main model is the SEM—(Schoolwide Enrichment Model). The present review shows a conspicuous production on gifted education, with the predominance of recently published articles (indicative of vivid interest in the topic) and of American origin. This geographic predominance, which does not cover the European and eastern parts of the world, may depend on the fact that the databases used [Scopus and Web of Science (WoS)] select results based on the use of English. This review reveals gaps and emerging trends in gifted education research, suggesting possibilities and future perspectives.